APPLICATION IN INDONESIA EARLY HUMANS USING MACROMEDIA FLASH 8.0 - Dina Oktaviani; Melani Dewi Lusita, SKom., MMSI (Jurnal Sistem Informasi, 2008)
This writing explains information about the types of early humans in Indonesia. Presentation made is in the form of applications using Macromedia Flash 8.0. This application is packaged as a fairly interesting and can be used as study materials and can facilitate students to learn more about the kinds of early humans that exist in Indonesia and its culture results.